Efforts to Implement the International Regulations for Preventing Collisions at Sea (COLREGS) to Prevent Collisions on Board the SPB. Sainty Giant - Sahrul Angga Saputra; Marthen Marthen; Sigit Sigit (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The implementation of the International Regulations for Preventing Collisions at Sea (COLREGs) 1972 is essential for ensuring navigational safety in Indonesia’s strategic waters, where dense international shipping traffic increases collision risks. Although COLREGs have been widely examined, studies specifically addressing watchkeeping responsibilities and navigational aid utilization on Self-Propelled Barges (SPB) in Indonesian crossing situations remain limited. This study aims to analyze the implementation of COLREGs in preventing collisions on SPB Sainty Giant, particularly during crossing situations. A descriptive qualitative approach with a case study design was employed, involving three informants consisting of the Chief Officer, Second Officer, and Able-Bodied Seaman, who were selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation studies, and were analyzed thematically through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of COLREGs on SPB Sainty Giant remains suboptimal, as reflected in watchkeeping officers arriving exactly at the start of their watch without sufficient handover time, crew fatigue caused by excessive daytime workload, and inadequate radar adjustment to weather conditions, which resulted in small vessels remaining undetected. These findings highlight the importance of watchkeeping discipline, navigational aid optimization, and crew competency in strengthening collision prevention. This study contributes to maritime navigation and safety literature by extending understanding of COLREGs application in SPB operations. The practical implications emphasize the need for shipping companies and ship masters to improve watchkeeping procedures, provide regular Radar ARPA training, and strengthen crew understanding of COLREGs through simulation-based training. Further research is recommended to examine COLREGs implementation across different vessel types and shipping routes in Indonesian waters.